KROMOSOM STICKY PADA KECAMBAH PADI (Oryza sativa L.) ASAL KABUPATEN BENGKALIS, RIAU TERKAIT CEKAMAN GARAM - Ermi Ningsih; Dewi Indriyani Roslim; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Rice (Oryza sativa L.) is a plant that is not resistant to the salt stress, but the development of agriculture in coastal areas requires the analysis of rice genotypes that are resistant to the salt stress. The salt stress may cause chromosomal abnormality, such as sticky chromosome. This study was aimed to analyze the influence of the salt stress on the formation of chromosomes in four rice genotypes originating from Bantan Air village, Bengkalis. This research was conducted using randomized block design (RBD) with two factors, i.e. NaCl concentrations (0 mM, 60 mM, 75 mM, and 90 mM) and the rice genotypes (IR64, Indragiri, Solok, Sadani, Yamin, and Amat Candu) with three replications for each treatment. Normal anaphase chromosomes were visible in control, whereas sticky chromosomes were seen in 90 mM salt exposure. It concluded that salt stress may cause sticky chromosomes.